Respuestas

  • Usuario de Brainly
2013-12-11T17:30:24+01:00
**( \frac{1}{2}+( \frac{3}{4} *\frac{1}{2}))* \frac{1}{2}=

( \frac{1}{2}+ \frac{3}{8})* \frac{1}{2}=

( \frac{4}{8}+ \frac{3}{8})* \frac{1}{2}=

\frac{7}{8}* \frac{1}{2}=  \frac{7}{16}

Solución: 7/16

**[(\frac{3}{4}+ \frac{1}{5})*( \frac{1}{10}+ \frac{3}{9}*( \frac{9}{6}))] =

[(\frac{3}{4}+ \frac{1}{5})*( \frac{1}{10}+ \frac{27}{45})] =

[(\frac{3}{4}+ \frac{1}{5})*( \frac{9}{90}+ \frac{54}{90})] =

[(\frac{3}{4}+ \frac{1}{5})*\frac{63}{90}] =

[(\frac{15}{20}+ \frac{4}{20})*\frac{63}{90}] =

[\frac{19}{20}*\frac{63}{90}] =  \frac{1197}{1800} =  \frac{399}{600} =  \frac{133}{200}

Solución: 133/200 (simplificado)